Analisa terhadap Kompensasi dan Jenjang Karir Sebagai Strategi dalam Meningkatkan Kinerja Karyawan di Triple SSS Cafe Pacet Mojokerto - Wahyudi, Imam (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2023)
The performance strategy improvement theory put forward by Kasmir, there are several factors that influence performance, both results and work behavior, are as follows: 1. Employee Abilities and Expertise. 2. Work Motivation, 3. Organizational Culture, 4. Leadership, 5. Job Satisfaction, 6. Work Discipline. Meanwhile, the impact of improving performance is that there are 2 factors that are influenced by performance, both directly and indirectly, namely (1) Compensation, namely the remuneration given by the company to its employees, (2) career path, which is an award given by the company to its employees. At Triple SSS Cafe Pacet Mojokerto, employees lack work discipline and do not obey regulations, however, Triple SSS Cafe Pacet Mojokerto's income is quite large and stable every month. The type of research used by researchers is field research using a qualitative approach. The data collection techniques used by researchers are interviews and observation. The results of this research are the use of strategies to improve employee performance at Triple SSS Cafe Pacet Mojokerto using the theory of work abilities and skills, work motivation, leadership, organizational culture, job satisfaction and work discipline. All aspects have been carried out well by Triple SSS Cafe Pacet Mojokerto, except for the work discipline aspect, there are still many employees who arrive late, leave for various reasons and have not obeyed the regulations made. In the career aspect, Triple SSS Cafe Pacet Mojokerto has not implemented career management for its employees. At Triple SSS Cafe Pacet Mojokerto, it only increases salaries for employees who have worked for a long time in stages as a form of loyalty to the company. Meanwhile, the compensation aspect has been implemented well.